Sufficient condition and partial sums of certain analytic functions / Busyra Latif - Latif, Busyra (2014)
In this study, we denote S as the class of normalized univalent functions in the unit disk E = {z: |z| < l} having the form: oo f{z)= z+ a2 z2 +a3 z3 +••• = z + ∑ ak zk k=2 We also denote T as the class of functions with negative coefficients. An analytic and univalent function g is in T if it has the form: g(z) = z - a2 z2 – a3 z3-••• =z - ∑ ak zk k=2